Corporate Strategy in Achieve the Objectives of Sustainable Development (SDGs) - Yanuar Ramadhan; Nelcie Mussa; Yuliana; Ika Ismiyar; Effendi Tjahjadi (Global Writing Academica Researching & Publishing, 2022)
This study aims to see sustainable development in realizing poverty alleviation, quality education, and reducing inequality in Indonesia. The literature study uses an approach by adopting the Participatory Rural Appraisal (PRA) model. The methodology used utilizes the literature study method by using theoretical references related to the problems that exist in the discussion of the sustainable development goals of the Papua province. The results of implementing sustainable development The Papuan Provincial Government has a planning commitment and has been made in the 2013-2018 Medium Term Development Plan (RPJMD) for efforts to reduce poverty, providing the Smart Indonesia Card (KIP) program as a key instrument to expand access to education for school students primary and secondary education, and for young people aged 6-21 years who have KIP, or from households that hold a Social Protection Card (KPS) education assistance is provided. The strategy that must be carried out in realizing the three sustainable developments is to invite private companies to help realize sustainable development which was proclaimed by the United Nations in September 2015.